2012 Third Workshop on Applications for Multi-Core Architecture 2012
DOI: 10.1109/wamca.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-Solution and Energy-to-Solution: A Comparison between ARM and Xeon

Abstract: Most High Performance Computing (HPC) systems today are known as "power hungry" because they aim at computing speed regardless to energy consumption. Some scientific applications still claim more speed and the community expects to reach exascale by the end of the decade. Nevertheless, to reach exascale we need to search alternatives to cope with energy constraints. A promising step forward in this direction is the usage of low power processors such as ARM. ARM processors target low power consumption in contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
0
14
0
3
Order By: Relevance
“…Padoin et al [32] compared an ARM Cortex-A9 1.0 GHz dual-core processor from Texas Instruments to two multiprocessors: one composed of two quad-core 2.4 GHz Intel Xeon E5 processors and the other composed of four 2.0 GHz 8-core Xeon X7 processors. They analyzed different metrics such as time-to-solution, peak power and energy-to-solution using 6 benchmarks from the NAS Parallel Benchmarks (NPB).…”
Section: Related Workmentioning
confidence: 99%
“…Padoin et al [32] compared an ARM Cortex-A9 1.0 GHz dual-core processor from Texas Instruments to two multiprocessors: one composed of two quad-core 2.4 GHz Intel Xeon E5 processors and the other composed of four 2.0 GHz 8-core Xeon X7 processors. They analyzed different metrics such as time-to-solution, peak power and energy-to-solution using 6 benchmarks from the NAS Parallel Benchmarks (NPB).…”
Section: Related Workmentioning
confidence: 99%
“…They modeled the degree of CPU core, memory, and I/O and estimated the clock frequency to achieve energy-efficient performance without compromising execution time. Edson et al analyzed the time-to-solution and energy-to-solution comparison of ARM and Intel Xeon and found that Xeon has still a better tradeoff from user's point-of-view [22]. They analyzed measurements on ARM Cortex-A8, Cortex-A9, and Intel Atom and SandyBridge using mobile, desktop, and server workloads.…”
Section: Related Studiesmentioning
confidence: 99%
“…Padoin et al [12] compared an ARM Cortex-A9 1.0GHz dual-core processor from Texas Instruments to two multiprocessors: one composed of two quad-core 2.4GHz Intel Xeon E5 processors and the other composed of four 2.0GHz 8-core Xeon X7 processors. They analyzed different metrics such as time-to-solution, peak power and energy-to-solution using 6 benchmarks from the NAS Parallel Benchmarks (NPB).…”
Section: Related Workmentioning
confidence: 99%
“…Research on the power efficiency and numerical kernel performances of both general purpose and low-power processors are quite common [12,14]. However, in this work we are interested in the analysis of the code adaptations needed to go from multicores to manycores.…”
Section: Introductionmentioning
confidence: 99%